Carbon fiber sizing agents based on renewable terpenes. (22nd March 2022) - Pawar, Sujit S.; Hutchinson, Sally A.; Eyckens, Daniel J.; Stojcevski, Filip; Hayne, David J.; Gengenbach, Thomas R.; Razal, Joselito M.; Henderson, Luke C.
Abstract: The optimization of fiber-matrix adhesion is a persistent challenge in any fiber-based composite materials. Usually, commercial sizing agents are applied to carbon fiber surfaces, but these are unknown complex mixtures of proprietary nature. Here, naturally derived terpenes, borneol and terpeniol, were chemically modified and used as sizing agents for carbon fibers. To tailor the surface interactions, carbon fibers possessing enriched surface exposed amines, thiols, and carboxylic acids were fabricated and sized. These novel sizing agents alone improve the IFSS of pristine fibers (up to +92%) in an epoxy resin. Surface modification also shows an increase the IFSS of pristine fibers prior to the addition of sizing (up to +142%). More critically, the IFSS is further enhanced when coupling surface modification techniques with application of sizing agents (up to +221% compared to unsized pristine fiber). This work offers a unique set of materials and untapped chemical pool for potential application in composites and interface tailoring. Graphical abstract: Image 1